Efficacy of three-dimensional visualization in mobile apps for patient education regarding orthognathic surgery. Issue 9 (September 2016) - Pulijala, Y.; Ma, M.; Ju, X.; Benington, P.; Ayoub, A.
Abstract: 'Sur-face' is an interactive mobile app illustrating different orthognathic surgeries and their potential complications. This study aimed to evaluate the efficacy of Sur-face by comparing two methods of delivering patient information on orthognathic surgeries and their related potential complications: a mobile app with interactive three-dimensional (3D) animations and a voice recording containing verbal instructions only. For each method, the participants' acquired knowledge was assessed using a custom-designed questionnaire. Participants in the 'app' group performed significantly better ( P < 0.0034) than those in the 'voice' group and retained more knowledge, suggesting that interactive visualizations play a key role in improving understanding of the orthognathic surgical procedure and its associated complications. This study emphasizes the impact of 3D visualizations in delivering information regarding orthognathic surgery and highlights the advantage of delivering validated patient information through mobile apps.